Accessibility and usability of e-government web-resources: problems and solutions - O. I. Dolganova; L. I. Vasilevskaya (Вестник университета)
The convenience and accessibility of e-government services largely determines the success in building/making/creating trusting online relationships with the population and reduces the inequality between different categories of citizens in terms of using online communications with public authorities. The purpose of the research is to identify the main flaws and problems in ensuring convenient and accessible use of public service portals by citizens on the basis of scientific and practical literature and to find approaches to their elimination. The article examines the foreign experience of creating comfortable conditions for electronic interaction of citizens with the government and lists the main errors in the development of interfaces and functionality of government websites and portals. In accordance with the international standards WCAG 2.1, the authors define the key criteria for the convenience and accessibility of web resources. Then they evaluate the compliance of the Gosuslugi web-portal with the formulated requirements and give recommendations on possible ways to improve Russian e-government web resources.